2008
DOI: 10.1592/phco.28.8.968
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Inappropriate Continuation of Acid Suppressive Therapy After Discharge in Patients Who Began Therapy in the Surgical Intensive Care Unit

Abstract: Most patients inappropriately continued to receive stress ulcer prophylaxis during post-SICU hospitalization. Presence of risk factors for stress ulcer-related gastrointestinal bleeding at SICU admission appears to influence continuation of AST after discharge from the hospital. A low percentage (3.2%) of patients was discharged home receiving inappropriate AST, yet overall, few study patients demonstrated a compelling risk factor for continuation of AST.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 25 publications
1
50
1
1
Order By: Relevance
“…Chang et al 6 showed that 74 of 206 patients received bronchodilators during mechanical ventilation without clinical indications, but they did not follow patients to discharge. The published literature [7][8][9][10][11][12][13][14][15][16] on inappropriate acid blockade is much larger, and the relationship with ICU stay has been previously described in community and tertiary centers nationally and internationally. Of 357 ICU patients given acid blockers, 24% were discharged on them with no clinical indication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chang et al 6 showed that 74 of 206 patients received bronchodilators during mechanical ventilation without clinical indications, but they did not follow patients to discharge. The published literature [7][8][9][10][11][12][13][14][15][16] on inappropriate acid blockade is much larger, and the relationship with ICU stay has been previously described in community and tertiary centers nationally and internationally. Of 357 ICU patients given acid blockers, 24% were discharged on them with no clinical indication.…”
Section: Discussionmentioning
confidence: 99%
“…15 Of 248 consecutive patients treated in a surgical ICU, 237 began acid blockers in the unit, 60 were discharged from the hospital with them, and only 3 "had a compelling risk factor." 16 We can only surmise that such perseverant treatment with bronchodilators and acid blockers is a medication error, an unintended artifact of critical care, most likely mechanical ventilation, where risks and costs are not offset by proven benefits.…”
Section: Discussionmentioning
confidence: 99%
“…A prospective case series of 248 consecutive patients admitted to a surgical ICU at a single institution evaluated the continuance of AST after the ICU discharge [Murphy et al 2008]. Patients were excluded if they received AST prior to ICU admission, had an appropriate indication for AST, had a gastroenterology consultation associated with the index admission, or died.…”
Section: Stress Ulcer Prophylaxis In the Critical Care Settingmentioning
confidence: 99%
“…5,[10][11][12] We found much lower baseline levels of discharge with inappropriate AST prescriptions. Although having pharmacy students on the patient care teams may have reduced the number of patients discharged with inappropriate AST prescriptions, this finding would be incidental.…”
Section: Discussionmentioning
confidence: 70%